Aktualisasi Pendidikan Agama Kristen terhadap Spiritual Peserta Didik di Era Digital - Bunga, Faldin Adrianus; Sinaga, Dina Anjely; Ritonga, Naomi Yolanti Octavia; Purba, Laura Paulina Dau Br; Tapparan, Joshua Mario (Journal of Knowledge and Collaboration, 2025)
The application of Christian religious education values in everyday life is important because with a good education pattern, especially in the family, it will have an impact on the spirituality of students both at home and at school. But what often happens so far is that there is no good education in schools or families. With the above problems, this article aims to explain again to every teacher and parent so that they are able to apply Christian values in everyday life. The purpose of this article is to provide a correct understanding in applying Christian values Efforts to improve the spirituality of students. The method used in this writing is a qualitative descriptive method with a Library approach from sources from scientific journals, books and also websites that can support this writing to apply Christian values in everyday life. The results of this article explain how important it is to apply Christian values in improving the spirituality of students, therefore Christian Religious Education can be implemented properly in accordance with the truth of God's Word.